INVESTIGATION OF SEASON AND LONG-TERM VARIATIONS OF NATURAL RADIONUCLIDES SPECIFIC ACTIVITY IN UNDERGROUND WATER - Yu. N. Goncharova; N. S. Shvidko; A. N. Kaduka (Радиационная гигиена)
An article contains the data on the investigations of season and long-term variations of radiation safety indexes of the water of some underground sources and centralized water-supply system of Tver city.